Mesenteric ischaemia following posterior myocardial infarction - Zafar, Mansoor (Clin Med (Lond), 2021)
An 84-year-old man was admitted with urinary tract infection and chest discomfort. He initially responded to conservative acute coronary syndrome management and antibiotics. On day 6 of admission, he developed acute severe abdominal pain; 12-lead electrocardiography showed widespread ST-segment depression in the anterior chest leads with ST-elevation in the posterior leads (V7–9) suggestive of an acute posterior myocardial infarction. Arterial blood gases showed severe metabolic acidosis with a lactate of 11 mmol/L. An urgent computed tomography angiography suggested acute small bowel ischaemia. The case was discussed with the on-call surgical team, who advised that, due to severe frailty, he was not fit for surgical intervention and should be managed conservatively. He was managed with intravenous heparin infusion and supportive measures, but sadly continued to deteriorate and was palliated. He died shortly afterwards.